2011
DOI: 10.1007/s12031-011-9621-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the MTHFR A1298C Variant in Leukoaraiosis

Abstract: Vascular demyelinization of the white matter of the brain is referred to as leukoaraiosis (LA). This very frequent entity is associated with a cognitive decline, thereby resulting in a deteriorating quality of life. Besides poorly controlled hypertension and aging, its development is reported to be associated with an elevated serum homocysteine level. Although the methylenetetrahydrofolate reductase (MTHFR) C677T genetic variant is associated with an elevated serum homocysteine level, it has not been proved to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These risk genes/polymorphisms are involved in a series of biological processes, including the regulation of cholesterol (e.g., ApoE, CETP) (Nebes et al, 2001;Hogh et al, 2007;Godin et al, 2009;Paternoster et al, Brought to you by | Carleton University OCUL Authenticated Download Date | 6/18/15 3:37 AM 2009; Qureischie et al, 2009), the regulation of systemic blood pressure and cerebral blood flow (e.g., ACE, AGT, AGTR1, CYP11B, F3) (Amar et al, 1998;Schmidt et al, 2001;Verpillat et al, 2001;Hassan et al, 2002;Henskens et al, 2005;van Rijn et al, 2007;Smith et al, 2009;), the biosynthesis of DNA and RNA (e.g., MTHFR) (Kohara et al, 2003;Linnebank et al, 2009;Hong et al, 2009;Szolnoki et al, 2012), immune response and inflammation (e.g., IL-6, IL5RA, ITGB6, CAPN10, NR3C1, KITLG) (Fornage et al, 2008;van Rossum et al, 2008;Smith et al, 2009;Fernandez-Cadenas et al, 2011), neuron regeneration (e.g., BDNF) (Taylor et al, 2008), neuroinflammation (e.g., MMP2, MMP3, MMP9, MMP13) (Fornage et al, 2007;Smith et al, 2009;Fernandez-Cadenas et al, 2011), cystoskeleton and cell adhesion (e.g., KNS2, ADD1, A2M, ICAM1) (van Rijn et al, 2006;Szolnoki et al, 2007;Fernandez-Cadenas et al, 2011;Fornage et al, 2011), and oxidative stress (e.g., PON1, NOS3) (Schmidt et al, 2000a;Henskens et al, 2005;Hadjigeorgiou et al, 2007;Fernandez-Cadenas et al, 2011). Although these risk genes/polymorphisms were shown to be strongly associated with the increased risk of LA, th...…”
Section: Candidate Gene Association Studymentioning
confidence: 99%
“…These risk genes/polymorphisms are involved in a series of biological processes, including the regulation of cholesterol (e.g., ApoE, CETP) (Nebes et al, 2001;Hogh et al, 2007;Godin et al, 2009;Paternoster et al, Brought to you by | Carleton University OCUL Authenticated Download Date | 6/18/15 3:37 AM 2009; Qureischie et al, 2009), the regulation of systemic blood pressure and cerebral blood flow (e.g., ACE, AGT, AGTR1, CYP11B, F3) (Amar et al, 1998;Schmidt et al, 2001;Verpillat et al, 2001;Hassan et al, 2002;Henskens et al, 2005;van Rijn et al, 2007;Smith et al, 2009;), the biosynthesis of DNA and RNA (e.g., MTHFR) (Kohara et al, 2003;Linnebank et al, 2009;Hong et al, 2009;Szolnoki et al, 2012), immune response and inflammation (e.g., IL-6, IL5RA, ITGB6, CAPN10, NR3C1, KITLG) (Fornage et al, 2008;van Rossum et al, 2008;Smith et al, 2009;Fernandez-Cadenas et al, 2011), neuron regeneration (e.g., BDNF) (Taylor et al, 2008), neuroinflammation (e.g., MMP2, MMP3, MMP9, MMP13) (Fornage et al, 2007;Smith et al, 2009;Fernandez-Cadenas et al, 2011), cystoskeleton and cell adhesion (e.g., KNS2, ADD1, A2M, ICAM1) (van Rijn et al, 2006;Szolnoki et al, 2007;Fernandez-Cadenas et al, 2011;Fornage et al, 2011), and oxidative stress (e.g., PON1, NOS3) (Schmidt et al, 2000a;Henskens et al, 2005;Hadjigeorgiou et al, 2007;Fernandez-Cadenas et al, 2011). Although these risk genes/polymorphisms were shown to be strongly associated with the increased risk of LA, th...…”
Section: Candidate Gene Association Studymentioning
confidence: 99%
“…These results are in disagreement with findings from studies of Caucasians from North America and people of European and Japanese descent, [14,16,21] but are consistent with findings from the study of Caucasians from Hungary. [1719] Although the significant association of rs1801133 TT with LA was missing after correction for multiple tests, the results indicated that rs1801133 TT may also act as a protective factor for LA similarly to rs3744028, rs1055129, and rs1135889, and it could significantly decrease LA risk in the recessive genetic model. This conclusion should be interpreted with caution owing to the ethnic differences described above and the following limitations in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[1315] Several candidate gene association studies have investigated and found a potential relationship between these 2 mutations and LA in several countries, such as North America, [16] Hungary, [1719] Germany, [20] and Japan. [21] However, neither SNP has been identified in GWAS of people of European descent, [10] nor have they been detected in the Chinese population.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that MTHFR C677T is associated with elevated serum homocysteine levels; clustering of MTHFR T 677C and A1298C heterozygous variants is moderately associated with the risk of L. MTHFR A1298C and 1298CC were associated with LA and were independent risk factors. MTHFR A1298C and 1298CC were associated with LA and were independent risk factors [105]. Rutten-Jacobs et al [125] conducted a meta-analysis of the European origin population, showing that MTHFR C677T is associated with lacunar stroke and LA volume, and is associated with hypertension.…”
Section: Homocysteine (Mthfr) Related Genesmentioning
confidence: 99%